To unite nuclear and sub-nuclear strong interactions - UV, Satya Seshavatharam; S, Lakshminarayana (International Journal of Physical Research, 2017)
With reference to ‘reciprocal’ of the strong coupling constant and ‘reduced Compton's wavelength’ of the nucleon, we make an attempt to understand the background of nuclear charge radius, binding energy and stability.